Arab–Malay Manuscripts at the North Sumatra State Museum as Evidence of Arab–Malay Cultural Interaction from the Perspectives of Philology and Cultural Historiography - Fahrul Ulum Feriawan; Wahyu Wardana; Annisa Hasanah (Warisan: Journal of History and Cultural Heritage, 2025)
This study examines the presence of Malay manuscripts preserved at the North Sumatra State Museum as historical evidence of cultural interaction between Arabs and Malays. Written predominantly in Jawi script, these manuscripts contain religious, legal, literary, and social texts that demonstrate the influence of Arab-Islamic intellectual traditions in the Malay world. Employing a qualitative descriptive method, this research investigates the provenance of the collections, museum acquisition mechanisms, conservation practices, and institutional interpretations of their historiographical significance. The findings indicate that the manuscripts were largely acquired through inter-museum collaboration, particularly with the Aceh Museum, and are preserved using preventive conservation measures to mitigate material degradation. This article argues that Arab–Malay manuscripts constitute not merely literacy artifacts but key sources for reconstructing intellectual networks, Islamic transmission, and cross-cultural exchanges in Sumatra, thereby positioning this study within broader Malay manuscript scholarship and Islamic Nusantara historiography. The study highlights the strategic role of museums in sustaining cultural memory and advancing manuscript-based historical research.